P203 Chronic pulmonary aspergillosis (CPA) in post tuberculosis sequele— aclinical experience from tertiary care. (20th September 2022) - Gupta, Chhavi; Agarwal, Meenakshi; Das, Shukla
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: Introduction: Chronic pulmonary aspergillosis (CPA) is a spectrum of illnesses clinically presenting as a persistent cough, dyspnea, hemoptysis, fatigue, and weight loss and radiologically can range from single aspergilloma, Aspergillus nodule, or chronic cavitary pulmonary aspergillosis (CCPA) which can progress to chronic fibrosing pulmonary aspergillosis if left untreated. 1 CPA has high morbidity, burden in India estimated to be in a 5-year prevalence of 24/100 000. 2 The commonly used criteria for diagnosing CPA include cough or hemoptysis for 1 month, raised Aspergillus -specific IgG, absence of positive GeneXpert test for Mycobacterium tuberculosis and either paracavitary fibrosis or a fungal ball on imaging of the thorax or progressive cavitation (either new cavitation or deterioration of pre-existing cavitation) on serial chest radiographs. Pulmonary tuberculosis (PTB) is the important predisposing risk factor for CPA, 3 India being an endemic country, incidence of CPA may be underestimated or it may be misdiagnosed as smear-negative tuberculosis. Microbiologically, diagnosis by direct confirmation of Aspergillus spp infection (microscopy or culture from respiratory samples) may not be always positive, in such a scenario the immune response to Aspergillus spp. by measuring Aspergillus specific Immunoglobulin Ig G in clinically suspected cases may be used for diagnosis of CPA. Method: This is a cross-sectional conducted in a tertiary care hospital, New Delhi, India. The patients with previous history of pulmonary tuberculosis who presented with symptoms of cough, hemoptysis, fever, shortness of breath, chest pain, and weight loss of ˃12-week duration were enrolled in the study. Relevant investigations including blood tests, chest imaging, sputum examination for bacterial infections, fungal (KOH mount), and tuberculosis (AFB smear, CBNAAT, mycobacterial cultures) were done. Microbiological evidence included a positive Aspergillus -specific IgG (cut off >8 units/ml) or positive serum galactomannan index (GMI) (cut off >1 according to EORTC/MSG guidelines) or KOH mount on sputum showing branching hyaline septate hyphae morphologically suggestive of Aspergillus spp. Patients who were diagnosed with CPA according to criteria were treated and followed up. Results: A total of 15 patients were screened in the study, 4 patients who had concurrently detected pulmonary tuberculosis detected by Genexpert, were excluded from the study. Majority of patients presented with complaints of recurrent episodes of cough and hemoptysis. Imaging features included cavitation, bronchiectasis, pleural thickening, and fungal ball. Sputum microscopy for fungal elements was positive only in 10 patients. The serum Aspergillus Ig G (values ranged from 19.8-200 u/mL) was raised in all patients while serum GMI above cut-off was present in only 5 patients. All confirmed CPA patients were managed with voriconazole for 4 months. Following 4 months of treatment, all patients had favorable outcomes in terms of radiological improvement and clinical cure. Conclusion: CPA is an underestimated post-PTB sequel and should be considered as differentials in patients with respiratory symptoms in post TB patients. Aspergillus Ig G and chest imaging are recommended as initial diagnostic tools for diagnosing CPA. Sources: Denning DW, Cadranel J, Beigelman-Aubry C et al. European Society for Clinical Microbiology and Infectious Diseases and European Respiratory Society. Chronic pulmonary aspergillosis: rationale and clinical guidelines for diagnosis and management. Eur Respir J. 2016; 47(1): 45-68. Agarwal R, Denning DW, Chakrabarti A. Estimation of the burden of chronic and allergic pulmonary aspergillosis in India. PLoS One. 2014; 9(12): e114745. Page ID, Byanyima R, Hosmane S et al. Chronic pulmonary aspergillosis commonly complicates treated pulmonary tuberculosis with residual cavitation. Eur Respir J. 2019; 53: 1801184